The role of quantitative methods in analyzing competition through quantities :A case study of OPEC and non-OPEC - Samir CHEKLELOU; Mohammed BENMERIEM (المجلة الدولية للأداء الاقتصادي)
This study aims to examine the type and degree of competition between OPEC and non-OPEC countries based on production volumes during the period from 1965 to 2023, using important quantitative tools. The study reached the following conclusions :The market share of non-OPEC countries is 1.5 times larger than that of OPEC countries on average .The volatility of OPEC countries' elasticity is greater than the volatility of non-OPEC countries' elasticity .The results of the VAR model showed a negative (positive) relationship between the production quantity of OPEC and non-OPEC countries, with an impact size of -0.32 (0.35). However, the production of non-OPEC countries does not significantly affect the production of OPEC countries .The Granger and Toda-Yamamoto tests proved the existence of a unidirectional causal relationship, specifically from OPEC countries' production to non-OPEC countries' production.